STRATEGI MANAJEMEN DAN PEMASARAN UNTUK MENINGKATKAN DAYA SAING PRODUK E-COMMERCE - Silalahi, Sukardi (Yayasan Education and Social Center, 2024)
This study aims to explore the strategies and challenges faced by Small and Medium Enterprises (SMEs) in Indonesia's e-commerce sector to enhance their competitiveness. Despite Indonesia being the largest e-commerce market in Southeast Asia, many SMEs struggle to adopt digital technologies and modern marketing strategies, creating a gap with larger enterprises. The research highlights that AI-based personalization and big data analytics are crucial for improving customer loyalty and understanding consumer preferences. Furthermore, integrating omnichannel strategies proves effective in strengthening customer relationships and boosting competitiveness. The findings suggest that SMEs require better access to digital tools, training, and policies supporting technology adoption to overcome these challenges. This study provides valuable insights into the digitalization of SMEs in Indonesia and offers strategies to enhance their competitiveness in the rapidly growing e-commerce market.